Reversible nickel-metallacycle formation with a phosphinimine-based pincer ligand. Issue 23 (27th May 2020) - Xing, Xiujing; Zhang, Shaoguang; Thierer, Laura M.; Gau, Michael R.; Carroll, Patrick J.; Tomson, Neil C.
Abstract : A phosphinimine-based pincer ligand was found to reversibly form nickel-containing metallacycles. Abstract : Pincer ligands have a remarkable ability to impart control over small molecule activation chemistry and catalytic activity; therefore, the design of new pincer ligands and the exploration of their reactivity profiles continues to be a frontier in synthetic inorganic chemistry. In this work, a novel, monoanionic NNN pincer ligand containing two phosphinimine donors was used to create a series of mononuclear Ni complexes. Ligand metallation in the presence of NaOPh yielded a nickel phenoxide complex that was used to form a mononuclear hydride complex on treatment with pinacolborane. Attempts at ligand metallation with NaN(SiMe3 )2 resulted in the activation of both phosphinimine methyl groups to yield an anionic, cis -dialkyl product, in which dissociation of one phosphinimine nitrogen leads to retention of a square planar coordination environment about Ni. Protonolysis of this dialkyl species generated a monoalkyl product that retained the 4-membered metallacycle. The insertion of 2, 6-dimethylphenyl isocyanide (xylNC) into this nickel metallacycle, followed by proton transfer, generated a new five-membered nickel metallacycle. Kinetic studies suggested rate-limiting proton transfer (KIE ≥ 3.9 ± 0.5) from the α-methylene unit of the putative iminoacyl intermediate.